Artificial intelligence-based risk communication for traveller protection in Indonesia - Fajri, Choirul; Sari, Norma; Karim Fathurrahman, Imam; Najih Farihanto, Muhammad; Fadillah, Dani (Universitas Ahmad Dahlan, 2025)
Indonesia, as a global tourism destination, faces various challenges in protecting tourists from the risks of natural disasters, health crises, and security threats. This study aims to analyze the use of Artificial Intelligence (AI) technology in risk communication systems for tourist protection in Indonesia. Through a systematic literature review approach, this study examines the concept of risk communication, the application of AI in tourism crisis management, and the implementation of this technology in the Indonesian context. The results show that AI has significant potential to improve the effectiveness of risk communication through early warning systems, information personalization, interactive chatbots, and predictive analytics. The implementation of AI in tourism risk communication in Indonesia requires integration between the Ministry of Tourism and Creative Economy, the National Disaster Management Agency, and the private sector. This study recommends the development of an AI framework that is responsive to local contexts, increased human resource capacity, and policies that support technological innovation in tourist protection. Importantly, this study contributes to the existing body of knowledge by providing a comprehensive framework that highlights how AI can be systematically integrated into national tourism safety strategies. It also offers practical insights for policymakers, tourism practitioners, and researchers in designing context-specific AI-based solutions for risk communication. By addressing theoretical and practical gaps, this research not only strengthens the academic discourse on AI in tourism but also supports the creation of safer and more resilient tourism destinations in Indonesia.